Pharmacological Activity From Various Parts of Palm Oil (Elaeis guineensis Jacq.): A Review - Widyowati, Retno; Putri, Anisa Yustikka; Sukardiman (Brawijaya University, 2025)
Background: Elaeis guineensis Jacq. belongs to Arecaceae family. This plant originates from West Africa and is spread across Asia such as Indonesia. Various parts have been used traditionally and proven by scientific experiments derived for various medicinal purposes for the treatment many disease because contains many phytonutrients. Objective: This study was to explore the pharmacological activities of Elaeis guineensis Jacq. from various parts and the potential compound content. Methods: The method was a literature review by searching research data about Elaeis guineensis Jacq. from 2010 to 2024 was derived from Pubmed, ScienceDirect, Scopus, SpringerLink, NCBI and Google Scholar with the keywords of Elaeis guineensis Jacq, palm oil, in vivo, in vitro, in silico and pharmacologycal activity. Results: Elaeis guineensis Jacq. has composition of bioactive constituents including vitamin E, fatty acid, fenolic, flavonoids, phenolics and karotenoid. With sample parts of leaves, fruits, seeds, and roots. Elaeis guineensis Jacq. has the ability as an pharmacology activity with the approach of in silico, in vitro and in vivo studies. The plant parts showed significant potential in various biological activities, including high antioxidant activity, significant antimicrobial effects against bacteria, anti-inflammatory, neuropharmacology, decreased blood glucose and insulin resistance, relatively safe toxicity tests at certain concentrations and protection against liver damage. The findings indicate the potential application in alternative medicine and nutraceutical development. Conclusion: Overall, this journal evaluated the pharmacological activities of various parts of Elaeis guineensis Jacq. through in silico, in vitro and in vivo pharmacological approaches showing that this species is a rich source of compounds. Further research is needed to develop therapeutic products based on Elaeis guineensis Jacq. including clinical trials to ensure safety and efficacy in humans.